Peningkatan Kualitas Pelayanan Klinik Pratama dengan Aplikasi Mommy-Be - Azniah Syam; Nilawati Uly; Abdul Malik; Imelda Iskandar; Lina Fitriani; Fatimah Jamir; Sharto Batti (Jurnal Pengabdian Ilmu Kesehatan, 2025)
Maternal and child health services in primary care facilities often face challenges in postpartum monitoring and lactation support. Information technology-based innovation is needed to efficiently improve service quality. This community service program aims to implement the Mommy-Be app, an mHealth app that supports lactation and infant growth and development, at the Zamzam Health Clinic (KSZ) as a model for innovation at Primary Clinics. Implementation methods included socialization of the app to health workers, hands-on training on how to use the app, and evaluation through pre- and post-knowledge tests and user satisfaction surveys. The results showed an increase in health workers' understanding of digital services, and all participants successfully used the Mommy-Be app's features in simulations. The clinic expressed its commitment to integrating Mommy-Be into routine services, accompanied by high enthusiasm for adopting technological innovations. This implementation contributed to improving the quality of postpartum and lactation care and supporting the Sustainable Development Goals (SDGs) in maternal-child health. The program also involved university students through the MBKM scheme, strengthening collaboration between academia and health services. In conclusion, the implementation of Mommy-Be successfully empowered health workers and encouraged digital transformation at the primary care level. In the future, the program has the potential to be replicated in other clinics with continued support for continued benefits to the community.